Índia e crescimento: modelos tradicionais e impacto da filosofia hindu - Ferreira, Vanessa Parra (2008)
Índia, with its notable economic expansion and its millenary culture and philosophy, is the theme of this work. A twofold objective is presented: exemplify several theoretical aspects of economic growth and deepen the study of an institutional aspect not widespread on the literature, the impact of religion. The first part of the text is focused on the economic reforms that were undertaken after the balance of payments crisis in 1991. Several theoretical studies are cited to contextualize the reforms’ impact on the growth potential. The external sector is deeply analyzed, followed by the private sector deregulation, mainly on industrial activity and price controls. Both sectors are jointly responsible for great part of the productivity surge (described by factor total productivity). Some aspects of monetary and fiscal policy are also analyzed, but less emphatically, as reforms and results in these sectors are limited. Moreover, an analysis on Hindu philosophy, predominant in the country, is presented. The theme is introduced with a brief description of the philosophical aspects, to be followed by the consequent economic impacts. Max Weber and Amartya Sen argue in different directions: Weber states that Hinduism and its magic would hinder rationalism; Sen firmly says Hinduism has a historical of heterodox rationalism, of contestation and creation. To settle the dispute an econometric model, based on conditional convergence, is developed: direct and indirect aspects are not significant. A debate is raised, one that may be an encouragement for some countries: a discouraging institutional historic, based on a controversial philosophy, may be overcame with correct economic reforms.